Electromagnetic Protection Hazards on Composite versus Metallic Aircraft - Moupfouma, Fidele; Klim, Zdzislaw; Skorek, Adam (SAE International journal of aerospace, 2013)
The lightning represents a fundamental threat to the proper operation of aircraft systems. For aircraft protection, Electromagnetic Compatibility requires conductive structure that will provide among all, electromagnetic shielding and protection from HIRF and atmospheric electricity threat. The interaction of lightning with aircraft structure, and the coupling of induced energy with harnesses and systems inside the airframe, is a complex subject mainly for composite aircraft. The immunity of systems is governed by their susceptibility to radiated or conducted electromagnetic energy. The driving mechanism of such susceptibility to lightning energy is the exposure to the changing magnetic field inside the aircraft and IR voltage produced by the flow of current through the structural resistance of the aircraft. The amplitude of such magnetic field and IR voltage is related to the shielding effectiveness of the aircraft skin (wiremesh, composite conductivity). However, it is also known that copper wiremesh does not provide adequate protection from magnetic field, even though it is needed for lightning current dissipation and the reduction of the heat that could damage the structure, following a lightning strike. The protection from magnetic field on composite aircraft can be provided by ferromagnetic material that nevertheless appears too heavy for covering the whole aircraft fuselage. Thus the need for R&D activities on nano technologies for solutions providing good magnetic shielding effectiveness without impacting aircraft weight. In the scope of aircraft Electromagnetic Protection and aircraft Safety activities, Bombardier Core Engineering is conducting R&D work on aircraft structure protection from lightning, and collaborating with University of Québec at Trois-Rivières (UQTR). This paper highlights the impact of magnetic field due to lightning on composite aircraft.